Isolation of atypical enteropathogenic Escherichia coli from chicken and chicken-derived products - Alonso, Mónica Zulema (2016)
Atypical enteropathogenic Escherichia coli (EPEC) strains from chicken and chicken-derived products were isolated and characterised. The strains presented a wide variety of serotypes, some have been reported in other animal species (O2:H40, O5:H40) and in children with diarrhoea (O8:H-). Most of the strains carried intimin β. The results indicate that chicken and chicken products are important sources of atypical EPEC strains that could be associated with human disease, and highlight the need to improve hygiene practices in chicken slaughtering and meat handling.